Lean UX agility through cross-functional collaboration - Gothelf, Jeff (O'Reilly Media, 2014)
"Designers have long relied on heavy documentation to communicate their vision for products and experiences. As technology has evolved to offer more complex and intricate interactions, the deliverables we've been creating have followed suit. Ultimately though, these deliverables have come to serve as bottlenecks to the creation process and as the beginning of the negotiation process with our team mates - a starting point for conversation on what could get built and launched. In this hands-on webcast you'll learn how Lean UX aims to open up the user experience design process with a collaborative approach that involves the entire team. It's a hypothesis-based design approach that tests design ideas early and often and, along the way, builds a shared understanding with our team mates that eliminates the dependencies on heavy documentation and challenging communications. Lean UX is a solution for the challenge of Agile and UX integration while it also works effectively in traditional waterfall and other hybrid environments."--Resource description page.
Title from title screen (viewed Oct. 31, 2014)
Keywords: User-centered system design; Human-computer interaction; Application software -- Development; Conception participative (Conception de systèmes); Logiciels d'application; Développement; Application software; Development; Electronic videos